The prevalence and impact of special issues in communications journals 2015–2019 - Repiso, Rafael; Segarra-Saavedra, Jesús; Hidalgo-Marí, Tatiana; Tur-Viñes, Victoria (John Wiley and Sons Inc, 2022)
This article analyses special issues, also referred to as thematic issues, monographic issues, or supplements, a mode of scientific journal publishing that has rarely been studied. It presents a bibliometric analysis of the production of journals in the field of communication in the period 2015–2019 and studies the impact of the publication of special issues in this field. The sample analysed includes 21,458 articles and reviews, 524 special issues, 418 publishers, and 94 journals. The study considers the presence of special issues in communication journals and the distribution and number of papers published in them and compares the impact of papers published in this mode with papers published in regular issues. The results reveal that 19% of articles and reviews published in the period studied appeared in special issues, which generally contain the same number of articles as regular issues. Moreover, 75% of journals achieved a higher average impact factor with articles published in special issues than they did with articles in regular issues. It is concluded that the publication of special issues appears to offer the potential benefits of attracting submissions, increasing profits, and improving impact, although it also has disadvantages. A reflection is offered on the strengths and weaknesses of this publishing practice.
Keywords: hirsch index; self-citation; bibliometric analysis; Scopus; JCR